The Sermon on the Mount, Utopia or Program for Action - Akkara, J (Journal of Dharma, 1989)
Pinchas Lapide, The Sermon on the Mount, Utopia or Program for Action, translated from German by Arlene Swidler, New York : Orbis Books, 1986, pp. vii + 148 (pbk) : 9. 95